Il teatro dell’io antitetico: Lo sdoppiamento dell’io nel teatro di Luigi Pirandello e in quello di William Butler Yeats - Balázs, Zsuzsanna (Verbum – Analecta Neolatina, 2015)
The present paper aims at pointing out the parallelism between Luigi Pirandello’s and W. B. Yeats’s interpretation of the mask, and the idea that in a human being there live more than one selves. This attempt is significant, because so far, the various similarities between their plays have been examined merely in the light of the two authors’ use of the techniques of the commedia dell’arte, and little attention has been paid to their concepts of the mask. I will illustrate that Yeats’s idea of the self and its anti-self (the mask or Daimon) bears strong relation to Pirandello’s interpretation of the distinction between the so-called persona and personaggio. Also, I will reveal the relationship between the characters’ mask and their madness, especially regarding the Stage Manager figures. Plays discussed include two Pirandellian comedies (Six Characters in Search of an Author and Henry IV) and two plays by Yeats (The Player Queen and The Shadowy Waters).